Effect of timing of protein and carbohydrate intake after resistance exercise on nitrogen balance in trained and untrained young men - Mori, H. (Journal of Physiological Anthropology, 2014)
Resistance exercise alters the post-exercise response of anabolic and catabolic hormones. A previous study indicated that the turnover of muscle protein in trained individuals is reduced due to alterations in endocrine factors caused by resistance training, and that muscle protein accumulation varies between trained and untrained individuals due to differences in the timing of protein and carbohydrate intake. We investigated the effect of the timing of protein and carbohydrate intake after resistance exercise on nitrogen balance in trained and untrained young men. Methods: Subjects were 10 trained healthy men (mean age, 23 ± 4 years; height, 173.8 ± 3.1 cm; weight, 72.3 ± 4.3 kg) and 10 untrained healthy men (mean age, 23 ± 1 years; height, 171.8 ± 5.0 cm; weight, 64.5 ± 5.0 kg). All subjects performed four sets of 8 to 10 repetitions of a resistance exercise (comprising bench press, shoulder press, triceps pushdown, leg extension, leg press, leg curl, lat pulldown, rowing, and biceps curl) at 80% one-repetition maximum. After each resistance exercise session, subjects were randomly divided into two groups with respect to intake of protein (0.3 g/kg body weight) and carbohydrate (0.8 g/kg body weight) immediately after (P0) or 6 h (P6) after the session. All subjects were on an experimental diet that met their individual total energy requirement. We assessed whole-body protein metabolism by measuring nitrogen balance at P0 and P6 on the last 3 days of exercise training. Results: The nitrogen balance was significantly lower in the trained men than in the untrained men at both P0 (P <0.05) and P6 (P <0.01). The nitrogen balance in trained men was significantly higher at P0 than at P6 (P <0.01), whereas that in the untrained men was not significantly different between the two periods. Conclusion: The timing of protein and carbohydrate intake after resistance exercise influences nitrogen balance differently in trained and untrained young men.